Reasoning about the Methods of Social Work - Khachatryan, Artak (Journal of Sociology: Bulletin of Yerevan University, 2015)
The article discusses the problems related to the definitions of Social Work Methods, particularly, the author is attempting to clarify the definitions of classical methods of Social Work - individual social work, social group work and community social work. The author expresses the opinion that in the process of implementation of Social Work profession in Armenia, no clear impression about these methods was formed. Especially in teaching rooms, in publications often the terms social group work method and community social work method are being used without a clear differentiation between cases, when the social worker is working with the group as a client and when he/she is working in the group, as an environment of functioning of individual. Adequately there is no clear understanding of cases, when the community is the client of the social worker and when it is an environment of functioning of the individual or group. The author suggests classifying the traditional methods of Social Work in two ways: 1. group/family and community methods of Social Work, considering that the social worker is working adequately in the group/family, and community and when the client is an individual, the group/family, and community – as an environment. 2. Individual, group/family, and community methods of Social Work, when the client is adequately the individual, the group/family and the community.
Keywords: social work method, case work method, group work method, community work method